2021
DOI: 10.1007/s10753-021-01559-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory Cytokines, Growth Factors and Adipokines in Adipogenesis and Insulin Resistance

Abstract: Obesity, manifested by increased adiposity, represents a main cause of morbidity in the developed countries, causing increased risk of insulin resistance and type 2 diabetes mellitus. Recruitment of macrophages and activation of innate immunity represent the initial insult, which can be further exacerbated through secretion of chemokines and adipocytokines from activated macrophages and other cells within the adipose tissue. These events can impact adipogenesis, causing dysfunction of the adipose tissue and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 103 publications
0
65
0
2
Order By: Relevance
“…Many pro-inflammatory cytokines are often elevated in overweight subjects with IR [ 18 ]. Recent studies also show that TNF-α, IL-6, and IL-1 promote IR, with TNF-α level as the main link between obesity and IR [ 19 , 20 ]. In this study, we did not observe a significant correlation between these cytokines and IR, while we found that IL-15 significantly and negatively correlated with METS-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Many pro-inflammatory cytokines are often elevated in overweight subjects with IR [ 18 ]. Recent studies also show that TNF-α, IL-6, and IL-1 promote IR, with TNF-α level as the main link between obesity and IR [ 19 , 20 ]. In this study, we did not observe a significant correlation between these cytokines and IR, while we found that IL-15 significantly and negatively correlated with METS-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in adipose tissue secretions such as increased free fatty acids and leptin levels and decreased adiponectin levels in obesity cause insulin resistance development (20). Also, increased secretion of pro-inflammatory cytokines (IL-6, TNF-α) plays a role in developing insulin resistance (28). For these reasons, the connection between obesity and insulin resistance is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional stress, especially excessive dietary fats, leads to obesity and insulin resistance. This process is believed to be the result of impaired insulin signal transduction caused by several molecules released from adipose tissue [ 40 , 41 ]. However, not all fatty acids have a negative effect on insulin sensitivity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%